Arthroscopy provides symptom relief and good functional outcomes in patients with hip synovial chondromatosis - Ferro, Fernando P. (J Hip Preserv Surg, 2015)
The purpose of this study was to evaluate clinical presentation, associated pathology and clinical outcomes after arthroscopic treatment of hip synovial chondromatosis (SC). A prospective data registry was queried for patients with SC diagnosis from 2005 to 2012. Surgical indications were intra-articular pain after failure of conservative treatment, labral pathology, chondral damage or loose bodies. All patients had femoroacetabular impingement based on radiographic findings. Patient-centered outcomes were collected before and after surgery. Standard hip arthroscopy techniques were used to address associated pathology. Twenty-three patients met the inclusion criteria. Eleven were males. Mean age was 43.7 years. Mean center-edge angle was 33.7 and alpha angle 73. Radiographs were diagnostic in five patients (23.8%). Magnetic resonance imaging identified loose bodies in 14 (66%). Most patients had an uncountable amount of loose bodies in the central and peripheral compartments. The most common associated pathology was a labral tear (100%) and acetabular cartilage injury (85%). All patients had improvement in range of motion. The average Modified Harris Hip score improved from 62 (pre-op) to 84.8 (post-op). Short-Form 12-PCS improved from 41 to 53. Western Ontario and McMaster Osteoarthritis Index improved from 27.1 to 7.2. Median overall satisfaction was 9.5 (out of 10). Hip arthroscopy with thorough removal of loose bodies and subtotal synovectomy, coupled with an aggressive and early rehabilitation program, was effective in ameliorating symptoms associated with from hip SC, yielding high levels of patient satisfaction and functional outcomes, in a 2.5 year follow-up time. Level of evidence: IV (case series)